2020
DOI: 10.2139/ssrn.3512774
|View full text |Cite
|
Sign up to set email alerts
|

Corporate Social Responsibility in Challenging and Non-Enabling Institutional Contexts: Do Institutional Voids Matter?

Abstract: The full-text may be used and/or reproduced, and given to third parties in any format or medium, without prior permission or charge, for personal research or study, educational, or not-for-prot purposes provided that: • a full bibliographic reference is made to the original source • a link is made to the metadata record in DRO • the full-text is not changed in any way The full-text must not be sold in any format or medium without the formal permission of the copyright holders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
140
0
1

Year Published

2020
2020
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(146 citation statements)
references
References 55 publications
(71 reference statements)
5
140
0
1
Order By: Relevance
“…ECSR in that year is considered as their impression management strategy to improve their legitimacy. ECSR of firms is regarded as an important signal of their legitimacy (Amaeshi, Adegbite, & Rajwani, ; Claasen & Roloff, ; Wei et al, ), representing “non‐substitutable green‐related capabilities” (Wei et al, , p. 210). The last important explanatory variable in the context of this research is DLSF, which is measured by calculating the number of firms that are being monitored in the stigmatized category in each province every year.…”
Section: Methodsmentioning
confidence: 99%
“…ECSR in that year is considered as their impression management strategy to improve their legitimacy. ECSR of firms is regarded as an important signal of their legitimacy (Amaeshi, Adegbite, & Rajwani, ; Claasen & Roloff, ; Wei et al, ), representing “non‐substitutable green‐related capabilities” (Wei et al, , p. 210). The last important explanatory variable in the context of this research is DLSF, which is measured by calculating the number of firms that are being monitored in the stigmatized category in each province every year.…”
Section: Methodsmentioning
confidence: 99%
“…Scholars have employed variety of theoretical underpinnings including, the institutional, legitimacy, and RBV perspectives in exploring CSR initiatives and activities (Flammer, ; Walker et al, ). The institutional perspective suggest that CSR initiatives, activities, and impact are collectively a function of the bundle of both formal and informal institutional arrangements (Amaeshi, Adegbite, & Rajwani, ; Walker et al, ). The inadequacy or otherwise of the interlocking formal and informal institutions constrain firms or provide them with opportunities to pursue certain strategic choices (Walker et al, ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Similarly, it is suggested that the nature of the NBS in the country in which it operates can determine whether a firm displays the explicit or implicit form of CSR (see also Hyatt & Berente, ; Jamali & Neville, ). Other studies, however, raise some doubts about the relevance of the NBS framework in its current form in contexts other than developed and western countries (Amaeshi, Adegbite, & Rajwani, ; Amaeshi, Adegbite, Ogbechie, et al, ; Forcadell & Aracil, ; Hofman et al, ; Jamali & Karam, ; Jamali & Neville, ; Muthuri & Gilbert, ; Wood & Frynas, ).…”
Section: Theoretical Perspectivesmentioning
confidence: 99%
“…First, managers who are implementing or planning to implement a sustainability agenda in the Malawian hospitality industry (or in other developing countries) should consider the influence of local institutional factors such as societal norms and expectations. This consideration may be vital in enhancing the success of their agendas and may also help them avoid a misallocation of resources (Amaeshi, Adegbite, & Rajwani, ). However, responding to local expectations does not necessarily mean abandoning the sustainability practices that may not be demanded by host societies.…”
Section: Implications For Managerial Practice and Public Policymentioning
confidence: 99%